Textile SIW Rectangular Ring-slot Antennas for Off-body Communication - Vašina, Petr (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2016)
In this paper, a textile SIW rectangular ring-slot antenna for the ISM frequency band 5.8 GHz is proposed. The antenna radiates a linearly polarized wave with the maximum radiation in the perpendicular direction to the antenna plane. The antenna is fabricated on the soft-shell fabric in the two versions. In the first version, the conductive layers were fabricated by a self-adhesive copper foil. In the second version, the conductive layers were fabricated by the screen printing on a foil ironed on the soft-shell fabric. Experimental results prove that the proposed antenna fabricated by copper foil achieves the impedance bandwidth of 3.1 % for the reflection coefficient less than -10 dB and the gain of 6.91 dBi. While screen printing antenna achieves the impedance bandwidth of 2.93 % for the reflection coefficient less than -10 dB and the gain of 7 dBi, respectively.
Keywords: wearable antenna; slot antenna; screen printing; substrate integrated waveguide